2018
DOI: 10.4178/epih.e2018008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of water-pipe smoking on birth weight: a population-based prospective cohort study in southern Iran

Abstract: OBJECTIVESConsecutive community health assessments revealed that water-pipe smoking in women and impaired growth in children were among the main health concerns in suburban communities in southern Iran. The aim of the present study was to identify the effects of water-pipe smoking during pregnancy on birth weight.METHODSData from a population-based prospective cohort study of 714 singleton live pregnancies in the suburbs of Bandar Abbas in southern Iran in 2016-2018 were used in this study. Data about water-pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…In the previous study on the cohort, we have shown that the incidence of low birth weight infants (i.e. birth weight below 2500 gram) was higher compared to other parts in Iran [33]. Therefore, it is presumed that low birth weight would effect on the type of delivery, especially choosing cesarean section.…”
Section: Discussionmentioning
confidence: 95%
“…In the previous study on the cohort, we have shown that the incidence of low birth weight infants (i.e. birth weight below 2500 gram) was higher compared to other parts in Iran [33]. Therefore, it is presumed that low birth weight would effect on the type of delivery, especially choosing cesarean section.…”
Section: Discussionmentioning
confidence: 95%
“…Adverse effects of water pipe on fetal growth have been the focus of very limited research in Iran. Cross-sectional research shows that compared to non-smokers, the odds of intrauterine growth retardation would increase by 2-3.5 times in water pipe smokers (6,7). On the other hand, a negative correlation is reported between infant`s mean birth weight and extent of maternal cigarette smoking (8).…”
Section: Introductionmentioning
confidence: 99%
“…Adverse effects of water pipe on fetal growth have been the focus of very limited research in Iran. Crosssectional research shows that compared to non-smokers, the odds of intrauterine growth retardation would increase by 2-3.5 times in water pipe smokers [6,7]. On the other hand, a negative correlation is reported between infant's mean birth weight and extent of maternal cigarette smoking [8].…”
Section: Introductionmentioning
confidence: 99%